2007
DOI: 10.1080/10913211.2007.10653842
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Terrorist Bombings on the Market Values of Hospitality and Tourism Enterprises: Global Evidence From Turkey, Spain, and Indonesia

Abstract: The last two decades witnessed numerous international terrorism incidents, some of which were specifically aimed at tourists or were at least intended to hamper visitor inflows. However, there is no empirical evidence explaining and measuring the effect of terrorist attacks on the market value of tourism enterprises. This study looked at the effect of the recent terrorist bombings in Bali (Indonesia), Istanbul (Turkey), and Madrid (Spain) on the market values of publicly traded hospitality and tourism firms in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In a more related stream of literature, studies typically link terror attacks to the performance of tourism stocks (see, for example, [12,[26][27][28][29]). A general message from these studies is that terrorism dampens tourism demand and hence leads to the poor performance of tourism stocks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a more related stream of literature, studies typically link terror attacks to the performance of tourism stocks (see, for example, [12,[26][27][28][29]). A general message from these studies is that terrorism dampens tourism demand and hence leads to the poor performance of tourism stocks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…After the tragedy of the 9/11 attacks that had significant economic repercussions on tourism industry across the world, researcher have also focused on the impacts of terrorism on tourism-related companies' performance. However, there are relatively few studies that have been devoted to analyze the response of tourism companies' stock returns to terror events and political tensions (see, for example, Drakos, 2004;Kim and Gu, 2004;Madanoglu et al, 2007;Chen, 2011;Chang and Zeng, 2011;Zopiatis, 2018). Overall conclusion of these studies is that terrorism causes poor performance of T&L stock returns.…”
Section: Introductionmentioning
confidence: 99%
“…We expect that tourism companies are sensitive to monetary policy actions due to high operating and financial risks. Although the effects of many macroeconomic factors and other events (Madanoglu et al, 2007;Demir et al, 2017; on stock returns have been investigated in the Turkish tourism industry, we encountered no study investigating monetary policy announcements. Thus, we aimed to examine the effect of policy rates announced by the CBRT on Borsa İstanbul (BIST) tourism stock returns.…”
Section: Methodsmentioning
confidence: 99%
“…Although there are many studies on tourism stock markets, various studies related to events affecting tourism stocks and returns are summarized below. In their research, Madanoglu et al (2007) aimed to examine the effects of terrorist bomb attacks in Indonesia, Turkey, and Spain on the market values of hospitality and tourism businesses. As expected, it was found that the markets reacted negatively to terrorist acts, and the market reaction in Turkey was weaker than that in Spain.…”
Section: Studies Related To the Tourism Stock Marketmentioning
confidence: 99%